Editorial - Chou, B. Ralph (Canadian Journal of Optometry, 2017)
Having attended both the CAO Congress and the American Academy of Optometry Annual Meeting this year, just like I did 38 years ago when I entered practice, I can look back across this time to see how our profession’s interests have developed and changed.